INDEKS MASSA TUBUH DAN KADAR KOLESTEROL DENGAN TEKANAN DARAH DI PUSKESMAS DARUSSALAM - Sinurat, Lasma Rina Efrina; Marbun, Agnes Silvina; Syapitri, Henny (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Hypertension is still one of the highest causes of death in the world. Factors that cause an increase in blood pressure include high blood cholesterol levels. The aim of this study was to determine the relationship between body mass index and total cholesterol levels with blood pressure (BP) in hypertensive patients at the Darussalam Community Health Center. This type of research uses observational analytics with a cross sectional approach. The research population was 90 people and the sample was 47 people using accidental sampling. Data collection tools use medical record data and observation sheets. The results of research on the characteristics of respondents showed that the majority of respondents' BMI was stage 1 obesity (36.2%), cholesterol levels (53.2%), and the majority of patients' systolic BP were stage I hypertension (48.9%), while the majority of patients' diastolic BP was normal. (36.2%). In the Sperm Rank test, a relationship was found between BMI and BP where the p value was 0.001 and the R value was 0.451, meaning there was a moderate correlation where the better the BMI, the more controlled the BP of hypertensive patients. Apart from that, there is also a relationship between total cholesterol levels and BP where the p value is 0.001 and the R value is 0.472, meaning that there is a moderate correlation where the better the cholesterol levels, the more controlled the BP of hypertensive patients. Thus, it is hoped that respondents will control their body weight and total cholesterol levels to avoid an increase in blood pressure in hypertensive patients.